Can we predict the microstructure of a non-woven flax/PLA composite through assessment of anisotropy in tensile properties?. (8th February 2022) - Pantaloni, Delphin; Ollier, Léa; Shah, Darshil U.; Baley, Christophe; Rondet, Eric; Bourmaud, Alain
Abstract: Flax/Poly-(lactide) non-woven composites are an alternative to conventional glass/poly-(propylene), offering a potentially lower environmental impact solution for the automotive industry. To understand this complex material, its detailed architecture and void distribution are examined through 3D microtomography. Anisotropy in fibre orientation is also observed, further verified through off-axis tensile tests. Then micro-mechanics and laminate theory are used, taking into account fibre orientation distribution, to predict mechanical properties and compare with experimental measurements. Even though some deviation is observed at off-axis angles greater than 45°, we report that off-axis tensile tests (property) can be used to predict fibre orientation (structure) in industrial production facilities as a simple means of quality control and tailored design of new non-woven preforms. Graphical abstract: Image 1 Highlights: Detailed microstructure analysis of flax/PLA non-woven composite. Preferential orientation of the fibres is observed inside the composite. This anisotropy is observed on tensile stiffness (transversal = 60% longitudinal). Off-axis tensile test can predict to indirectly the fibre orientation distribution.